Comparison of Dissolved Gas Analysis (DGA) Between Mineral Oil, Neutural Ester, and Palm Oil With Nano-Particle BaTiO3 - Triani Laohapongpan; Wiboon Promphanich; Chanin Boonlaksananusorn; Siwakorn Jeenmuang; Norasage Pattanadech (My University, 2024)
The dielectric liquid properties can be improved by adding suitable nano-particles to increase the dielectric and other properties. The BaTiO3 has been interesting for a decade for use to improve the liquid insulation characteristics. Such nanoparticles were used to mixed with mineral oil, natural ester, and palm oil. This paper focuses on a comparison of mineral oil, natural ester, and palm oil with BaTiO3 by the Dissolved Gas Analysis (DGA) technique. Hydrogen (H2), Methane (CH4), Acetylene (C2H2), Ethylene (C2H4), Ethane (C2H6), Carbon Monoxide (CO), Carbon dioxide (CO2) were mainly considered gases to compare because they are in the gas limitation used to diagnose a transformer problem. This researcher found that palm oil produces the most gas after undergoing thermal stress but its generating trend was better than others because the gas-producing rate decreases at higher temperatures.
Keywords: Polymer Nanocomposites and Properties